Results of experimental evaluation of the possibility of using an annular nozzle with a flat central body as part of a stand liquid rocket engine chamber - A. A. Kirshina; A. A. Levikhin; A. Yu. Kirshin (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
One of the ways to increase the efficiency of a rocket engine chamber is to ensure the fixed nozzle operation in the design mode over the entire range of altitudes (ambient pressure) of engine operation. The paper presents the results of a full-scale experiment of the annular nozzle model with a flat central body. The purpose of the experiment was to evaluate the efficiency in terms of the specific impulse of the annular nozzle with a flat central body in comparison with the Laval nozzle. The tests were carried out at the “hot” bench of the Department “Engines and Power Plants of Aircraft” BSTU “VOENMEH” named after D.F. Ustinov. The generated high-temperature steam-gas was used as a working fluid, the experiment was carried out under terrestrial conditions. During the stand testing the readings of operating parameters (pressure, mass flow, thrust, components ratio) were recorded in automated mode. The parameters were changed by reconfiguring the appropriate elements of the pneumohydraulic system. Based on the processed results of the tests the efficiency of the annular nozzle with a flat central body was evaluated in comparison with the Laval nozzle, and the values of the experimental data were verified with the theoretically expected ones.